2003
DOI: 10.1097/00004032-200304000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Patient Surface Radiation Doses at Two Pet Imaging Facilities

Abstract: To develop a practical means of auditing the procedures and to optimize the administered radionuclide activity, patient surface radiation doses following the administration of 18FDG for PET imaging have been measured at breast and gonad locations at two PET facilities. Patient dosimetry was performed using LiF TLD-100 chips placed near the breasts and gonads for 2 h following tracer injection. Standard uptake values from the image-reconstruction algorithms of one PET camera were investigated in regions of inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Our estimation about internal radiation was comparable to the values from the literature. Gonzalez et al [42] found that skin radiation doses to the right breast during FDG PET for the injected activity of 185 MBq was about 2.91 ± 0.83 mGyÁMBq -1 .…”
Section: Discussionmentioning
confidence: 99%
“…Our estimation about internal radiation was comparable to the values from the literature. Gonzalez et al [42] found that skin radiation doses to the right breast during FDG PET for the injected activity of 185 MBq was about 2.91 ± 0.83 mGyÁMBq -1 .…”
Section: Discussionmentioning
confidence: 99%